Prediction of 2000 m indoor rowing performance using a 30 s sprint and maximal oxygen uptake - Riechman, S. E.; Zoeller, R. F.; Balasekaran, G.; Goss, F. L.; Robertson, R. J. (Journal of Sports Sciences, 2002)
The aim of this study was to predict indoor rowing performance in 12 competitive female rowers (age 21.3 +/- 3.6 years, height 1.68 +/- 0.54 m, body mass 67.1 +/- 11.7 kg; mean +/- s) using a 30 s rowing sprint, maximal oxygen uptake and the blood lactate response to submaximal rowing. Blood lactate and oxygen uptake (VO2) were measured during a discontinuous graded exercise test on a Concept II rowing ergometer incremented by 25 W for each 2 min stage; the highest VO2 measured during the test was recorded as VO2max (mean = 3.18 +/- 0.35 l.min-1). Peak power (380 +/- 63.2 W) and mean power (368 +/- 60.0 W) were determined using a modified Wingate test protocol on the Concept II rowing ergometer. Rowing performance was based on the results of the 2000 m indoor rowing championship in 1997 (466.8 +/- 12.3 s). Laboratory testing was performed within 3 weeks of the rowing championship. Submitting mean power (Power), the highest and lowest five consecutive sprint power outputs (Maximal and Minimal), percent fatigue in the sprint test (Fatigue), VO2max (l.min-1), VO2max (ml.kg-1.min-1), VO2 at the lactate threshold, power at the lactate threshold (W), maximal lactate concentration, lactate threshold (percent VO2max) and VEmax (l.min-1) to a stepwise multiple regression analysis produced the following model to predict 2000 m rowing performance: Time2000 = -0.163 (Power) -14.213.(VO2max l.min-1) +0.738.(Fatigue) 7.259 (R2 = 0.96, standard error = 2.89). These results indicate that, in the women studied, 75.7% of the variation in 2000 m indoor rowing performance time was predicted by peak power in a rowing Wingate test, while VO2max and fatigue during the Wingate test explained an additional 12.1% and 8.2% of the variance, respectively.